Frailty in patients undergoing transcatheter aortic valve replacement: prognostic value of the Geriatric Nutritional Risk Index. Issue 3 (25th March 2021) - Seoudy, Hatim; Al‐Kassou, Baravan; Shamekhi, Jasmin; Sugiura, Atsushi; Frank, Johanne; Saad, Mohammed; Bramlage, Peter; Seoudy, Anna Katharina; Puehler, Thomas; Lutter, Georg; Schulte, Dominik M.; Laudes, Matthias; et al.
Abstract: Background: Malnutrition is a hallmark of frailty, is common among elderly patients, and is a predictor of poor outcomes in patients with severe symptomatic aortic stenosis (AS). The Geriatric Nutritional Risk Index (GNRI) is a simple and well‐established screening tool to predict the risk of morbidity and mortality in elderly patients. In this study, we evaluated whether GNRI may be used in the risk stratification and management of patients undergoing transcatheter aortic valve replacement (TAVR). Methods: Patients with symptomatic severe AS ( n  = 953) who underwent transfemoral TAVR at the University Hospital Schleswig‐Holstein Kiel, Germany, between 2010 and 2019 (development cohort) were divided into two groups: normal GNRI ≥ 98 (no nutrition‐related risk; n  = 618) versus low GNRI < 98 (at nutrition‐related risk; n  = 335). The results were validated in an independent (validation) cohort from another high‐volume TAVR centre ( n  = 977). Results: The low‐GNRI group had a higher proportion of female patients (59.1% vs. 52.1%), higher median age (82.9 vs. 81.8 years), prevalence of atrial fibrillation (50.4% vs. 40.0%), median logistic EuroSCORE (17.5% vs. 15.0%) and impaired left ventricular function (<35%: 10.7% vs. 6.8%), lower median estimated glomerular filtration rate (50 vs. 57 mL/min/1.73 m 2 ) and median albumin level (3.5 vs. 4.0 g/dL) compared with the normal‐GNRI group. Among peri‐procedural complications, Acute Kidney Injury Network (AKIN) Stage 3 was more common in the low‐GNRI group (3.6% vs. 0.6%, p  = 0.002). After a mean follow‐up of 21.1 months, all‐cause mortality was significantly increased in the low‐GNRI group compared with the normal‐GNRI group ( p  < 0.001). This was confirmed in the validation cohort ( p  < 0.001). Low GNRI < 98 was identified as an independent risk factor for all‐cause mortality (hazard ratio 1.44, 95% CI 1.01–2.04, p  = 0.043). Other independent risk factors included albumin level < median of 4.0 g/dL, high‐sensitive troponin T in the highest quartile (> 45.0 pg/mL), N ‐terminal pro‐B‐type natriuretic peptide in the highest quartile (> 3595 pg/mL), grade III–IV tricuspid regurgitation, pulmonary arterial hypertension, life‐threatening bleeding, AKIN Stage 3 and disabling stroke. Conclusions: Low GNRI score was associated with an increased risk of all‐cause mortality in patients undergoing TAVR, implying that this vulnerable group may benefit from improved preventive measures.